A novel SERS-based aptasensor for ultrasensitive sensing of microcystin-LR. (25th April 2019) - He, Deyun; Wu, Zhengzong; Cui, Bo; Jin, Zhengyu
Highlights: A SERS-based aptasensor was fabricated for MC-LR detection. The problem of the conventional immunological technique was overcome. LOD was as low as 0.002 ng/mL. Abstract: We developed a novel aptasensor based on surface enhanced Raman spectroscopy (SERS) and applied it for highly sensitive detection of microcystin-LR (MC-LR). In this work, MC-LR aptamer and its corresponding complementary DNA fragments (cDNA) were conjugated to gold nanoparticles (AuNPs) and magnetic nanoparticles (MNPs), respectively. Then, MC-LR aptamer-AuNPs and cDNA-MNPs conjugates were used as signal probes and capture probes, respectively. The proposed assay exhibited a linearity range from 0.01 to 200 ng/mL with the limit of detection (LOD) of 0.002 ng/mL. In addition, the reliability of the novel approach was validated by detecting different levels of MC-LR spiked in tap water samples. Overall, the novel aptasensor paves a new way for rapid and accurate determination of MC-LR and can be referred to detect other hazardous substances in water products.